Evaluation of eltrombopag in patients with aplastic anemia in real-world experience. (2019) - Konishi, Akiko; Nakaya, Aya; Fujita, Shinya; Satake, Atsushi; Nakanishi, Takahisa; Azuma, Yoshiko; Tsubokura, Yukie; Saito, Ryo; Hotta, Masaaki; Yoshimura, Hideaki; Ishii, Kazuyoshi; Ito, Tomoki; et al.
Highlights: The use of eltrombopag was expanded to cover AA in Japan in August 2017. The overall response rate was 55% (6/11). Four patients had recovery of all three cell lineages, and two patients had only neutrophil recovery. Stage at the initial assessment, the neutrophil-to-lymphocyte ratio and platelet counts were significantly different between the responders and non-responders. Abstract: Background: Although eltrombopag has recently been approved for treating AA, the effects of its clinical use remain unknown. Methods: We retrospectively analyzed 11 patients with AA, who had been treated with eltrombopag from August 2017 to May 2018. Results: Overall response rate was 55%. There was tri-lineage recovery in four patients and platelet recovery in two. The reactive time was within 8 weeks after treatment initiation. Stage at the initial assessment, the neutrophil-to-lymphocyte ratio and platelet counts were significantly different between the responders and non-responders. Conclusion: Eltrombopag is a promising agent for treating patients with any degree of AA.